2016
DOI: 10.1038/srep31433
|View full text |Cite
|
Sign up to set email alerts
|

Salt secretion is linked to acid-base regulation of ionocytes in seawater-acclimated medaka: new insights into the salt-secreting mechanism

Abstract: Ionocytes in the skin and gills of seawater (SW) teleosts are responsible for both salt and acid secretion. However, the mechanism through which ionocytes secrete acid is still unclear. Here, we hypothesized that apical Na+/H+ exchangers (NHE2/3), carbonic anhydrase (CA2-like), and basolateral HCO3−/Cl− exchanger (AE1) are involved in acid secretion. In addition, the hypothesized involvement of basolateral AE1 suggested that acid secretion may be linked to Cl− secretion by ionocytes. The scanning ion-selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…Despite its very low expression, sea bass nhe2c is about 28 times more expressed in SW than in FW suggesting its role in acid secretion as reported previously for several nhe2/3 paralogs in SW (Chen et al, 2017;Claiborne et al, 1999;Liu et al, 2016). Contrary to trout nhe2, sea bass nhe2b and nhe2c…”
Section: Accepted Manuscriptsupporting
confidence: 62%
See 1 more Smart Citation
“…Despite its very low expression, sea bass nhe2c is about 28 times more expressed in SW than in FW suggesting its role in acid secretion as reported previously for several nhe2/3 paralogs in SW (Chen et al, 2017;Claiborne et al, 1999;Liu et al, 2016). Contrary to trout nhe2, sea bass nhe2b and nhe2c…”
Section: Accepted Manuscriptsupporting
confidence: 62%
“…3 killifish cuboidal cells, Na + uptake seems not to be coupled to active proton excretion in this species (Katoh et al, 2003). There is also evidence that NHE2 and NHE3 are expressed in gill ionocytes of teleosts maintained in seawater (SW), playing critical roles in acid secretion (Chen et al, 2017;Claiborne et al, 1999;Liu et al, 2016;Weihrauch et al, 2009). In many teleost species, nhe3 mRNA expression is high in FW compared to SW (Bollinger et al, 2016;Hiroi et al, 2008;Inokuchi et al, 2008;Watanabe et al, 2008) except in the climbing perch Anabas testudineus, where the opposite pattern has been shown with increased nhe3 mRNA and NHE3 protein expression in SW (Chen et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In SW fish, NHE in the apical membrane of ionocytes is thought to be the major transporter for acid secretion (Claiborne et al, 2002). In medaka gills, mRNA levels of NHE2 and NHE3 were upregulated by acidified SW ( pH 7), suggesting that NHE was involved in acid secretion by SW-type ionocytes (Liu et al, 2016). Moreover, applying the scanning ion-selective electrode technique (SIET), Liu et al (2013Liu et al ( , 2016 have shown that treatment with an inhibitor of NHE suppressed both H + and Cl − secretion at ionocytes of SWacclimated medaka larvae.…”
Section: Discussionmentioning
confidence: 99%
“…In medaka gills, mRNA levels of NHE2 and NHE3 were upregulated by acidified SW ( pH 7), suggesting that NHE was involved in acid secretion by SW-type ionocytes (Liu et al, 2016). Moreover, applying the scanning ion-selective electrode technique (SIET), Liu et al (2013Liu et al ( , 2016 have shown that treatment with an inhibitor of NHE suppressed both H + and Cl − secretion at ionocytes of SWacclimated medaka larvae. These findings indicate that NHE2 and NHE3 play critical roles in acid secretion, and that the acid secretion is linked to Cl − secretion in SW.…”
Section: Discussionmentioning
confidence: 99%
“…In fishes, ionic regulation and acid-base balance are intricately linked because of the tight coupling of apical Na + /H + exchange through Nhe3 in branchial ionocytes (Evans et al, 2005 ; Perry and Gilmour, 2006 ). Ionocytes in fish gills respond to changes in pH and salinity of the external environments through the concurrent activation of acid-base regulatory and osmoregulatory mechanisms, and Nhe3 is implicated as the relevant transporter (Furukawa et al, 2011 ; Liu et al, 2016 ). Furthermore, acid-base regulation, ammonia excretion, and osmoregulation have been shown to be closely linked in the seawater-inducible ionocytes of medaka acclimated to seawater (Liu et al, 2013 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%